(untitled) (Scientific journal of the Fergana State University, 2024)
This article reveals the consequences of the colonial policy of the economic system, tax system, agricultural situation and irrigation facilities on a scientific basis. The issues of mastery of the colonial policy, purpose and reimbursement of the colonial policy of the empire is also covered by the development of the raw material, strengthening the raw material market.